Integrasi Literasi Digital dan Karakter Islami Berbasis Artificial Intelligence - Taufik Mastiyar; Mulyapradana, Aria; Prayetno, Paimin Hadi; Hasim, Muhammad (Jurnal Pemberdayaan Umat, 2026)
Purpose: This study aims to implement "Kuis Pintar SD," a mobile learning application integrated with Generative Artificial Intelligence (GenAI), to foster digital literacy and internalize Islamic character values among students at the At-Tanzil Hicom Community Learning Center, Malaysia. Research Methodology: The program employed a Participatory Action Research (PAR) approach encompassing four stages: needs analysis, development using React Native and Google Gemini API, implementation through workshops, and formative evaluation. The intervention involved 25 elementary-level students with diverse learning abilities. Results: The research produced a functional, adaptive application where GenAI acts as an intelligent tutor capable of generating dynamic Islamic Education (PAI) content. Quantitative observation indicated a surge in active participation from 65% in conventional sessions to 92% during AI-assisted activities. Crucially, the AI’s "Intelligent Explanation" feature successfully bridged technical literacy with moral development by providing contextual reasoning (hikmah) for Islamic ethics, shifting learning from rote memorization to value internalization. Conclusions: Integrating Generative AI into mobile learning serves as an effective medium for delivering adaptive and value-based education in informal migrant community settings. Limitations: Implementation was constrained by internet instability and limited device availability. Contributions: This study offers a replicable model for utilizing GenAI to enhance character education within marginalized communities.